Wybrane dochody budżetów gmin przekazywane z budżetu państwa w układzie przestrzennym w Polsce w latach 2004–2011 - Opałka, Benedykt (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
After Poland’s accession to EU regional and local development as well as public administration actions for improvement of conditions of living were tied with the necessity to invest heavily, especially in infrastructure. Providing necessary funds meant combining funds from different sources, particularly from public resources and from the EU budget. In the present system of financing the tasks of local government, external income, transferred to the local government through national budget, is important part of development policy, even though it limits financial self-reliance of local government. Income transferred to gminas from national budget, especially the gminas’ share of personal income tax, still plays important part in their budgets. The amount of money transferred to gminas to co-finance with EU different projects and programs shows large spatial differences which influences the level of investments, especially in infrastructure.